Enhancing and Complementary Mechanisms of Synergistic Action of Acori Tatarinowii Rhizoma and Codonopsis Radix for Alzheimer's Disease Based on Systems Pharmacology. (25th June 2020) - Liu, Shengwei; He, Cui; Liao, Yuan; Liu, Hailin; Mao, Wanli; Shen, Zhengze
Abstract : Background and Aim . Alzheimer's disease (AD) is a common neurological disorder worldwide. In traditional Chinese medicine (TCM), Acori Tatarinowii Rhizoma (ATR) and Codonopsis Radix (CR) are common herbs used to treat AD. However, due to the many active ingredients and targets in these herbs, it is difficult to clarify the synergistic mechanism of ATR and CR. To reveal the multicomponent synergistic mechanism of ATR and CR in Alzheimer's disease, we analyzed important components, drug targets, and crucial pathways using a systems pharmacology strategy. Materials and Methods . In this study, a systems pharmacology-based strategy was used to elucidate the synergistic mechanism of Acori Tatarinowii Rhizoma and Codonopsis Radix for the treatment of AD. This novel systems pharmacology model consisted of component information, pharmacokinetic analysis, and pharmacological data. Additionally, the related pathways were compressed using the Kyoto Encyclopedia of Genes and Genomes (KEGG) database, and the organ distributions were determined in the BioGPS bank. Results . Sixty-eight active ingredients with suitable pharmacokinetic profiles and biological activities were selected through ADME screening in silico . Based on 62 AD-related targets, such as APP, CHRM1, and PTGS1, systematic analysis showed that these two herbs were mainly involved in the PI3K-Akt signaling pathway, MAPK signaling pathway, neuroactive ligand-receptor interaction, and fluid shear stress and atherosclerosis, indicating that they had a synergistic effect on AD. However, ATR acted on the KDR gene, while CR acted on IGF1R, MET, IL1B, and CHUK, showing that they also had complementary effects on AD. The ingredient contribution score involved 29 ingredients contributing 90.14% of the total contribution score of this formula for AD treatment, which emphasized that the effective therapeutic effects of these herbs for AD were derived from both ATR and CR, not a single herb. Organ distribution showed that the targets of the active ingredients were mainly located in the whole blood, the brain, and the muscle, which are associated with AD. Conclusions . In sum, our findings suggest that the systems pharmacology methods successfully revealed the synergistic and complementary mechanisms of ATR and CR for the treatment of AD.